Inhibitors supercharge kinase turnover through native proteolytic circuits - Natalie S. Scholes; Martino Bertoni; Arnau Comajuncosa-Creus; Katharina Kladnik; Xuefei Guo; Fabian Frommelt; Matthias Hinterndorfer; Hlib Razumkov; Polina Prokofeva; Martin P. Schwalm; Florian Born; Sandra Roehm; et al. (Nature, 2026)
Abstract Targeted protein degradation is a pharmacological strategy that relies on small molecules such as proteolysis-targeting chimeras (PROTACs) or molecular glues, which induce proximity between a target protein and an E3 ubiquitin ligase to prompt target ubiquitination and proteasomal degradation 1 . Sporadic reports indicated that ligands designed to inhibit a target can also induce its destabilization 2–4 . Among others, this has repeatedly been observed for kinase inhibitors 5–7 . However, we lack an understanding of the frequency, generalizability and mechanistic underpinnings of these phenomena. Here, to address this knowledge gap, we generated dynamic abundance profiles of 98 kinases after cellular perturbations with 1,570 kinase inhibitors, revealing 160 selective instances of inhibitor-induced kinase destabilization. Kinases prone to degradation are frequently annotated as HSP90 clients, therefore affirming chaperone deprivation as an important route of destabilization. However, detailed investigation of inhibitor-induced degradation of LYN, BLK and RIPK2 revealed a differentiated, common mechanistic logic whereby inhibitors function by inducing a kinase state that is more efficiently cleared by endogenous degradation mechanisms. Mechanistically, effects can manifest by ligand-induced changes in cellular activity, localization or higher-order assemblies, which may be triggered by direct target engagement or network effects. Collectively, our data suggest that inhibitor-induced kinase degradation is a common event and positions supercharging of endogenous degradation circuits as an alternative to classical proximity-inducing degraders.